The Decades of Carvalho Calero. His Evolving Role in the Standardisation and Regeneration of the Galician Language - Freixeiro Mato , Xosé Ramón; Sánchez Rei , Xosé Manuel (Madrygal. Revista de Estudios Gallegos, 2023)
Ricardo Carvalho Calero played a central role in the process of standardisation and regeneration of Galician in the 20th century through a revival strategy based on the elimination of Spanishisms and a possible convergence with Portuguese. Over the course of his life, he adapted his approach to standardisation to match his own philological evolution and the sociopolitical circumstances of the time. In the decade prior to the Spanish Civil War, he joined the Seminary of Galician Studies. In the 1940s, he became a target of repression by the newly installed regime, and in the 1950s he joined the Galaxia publishing project, where he supported proposals for a simplified spelling system. During the final decades of his life, he remained one of the most influential voices in the debate over standardisation: widely admired for his intellectual achievements, he was the foremost scholar of Galician literature, became the first lecturer and later professor of Galician Linguistics and Literature at the University of Santiago de Compostela, and authored the most popular and widely read grammar of Galician of his time.
Keywords: Carvalho Calero; Standardisation; Galician; Galician grammar; Portuguese; Reintegrationism